Differential effects of GLP-1 receptor agonists on diabetic osteopathy in type 2 diabetes: a patient-stratified network meta-analysis - Yazan Jumah Alalwani; Ali Saad Alshahrani; Aseel Ibrahem Alsudays; Reema Nasser Awad Almutairi; Rana Ali Hassan Arab; Reema Safar Ali Alqahtani; Omar Saad Alrefaei; Rana Alqahtani; Meshal Salman Bin Ofaysan; Ahmed Y. Azzam; Ammar K. Alomran (BMC Musculoskeletal Disorders)
Abstract Introduction Diabetic osteopathy is a skeletal disorder that is characterized by increased fracture risk despite normal bone mineral density. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have emerged as important therapeutic agents for type 2 diabetes mellitus (T2DM), but their effects on diabetic bone disease were not studied nor investigated sufficiently in previous studies in the literature. We conducted a network meta-analysis to evaluate the differential effects of GLP-1 RAs on bone health outcomes in patients with T2DM. Methods We performed a systematic review and network meta-analysis of randomized controlled trials evaluating GLP-1 RAs with bone-related outcomes in T2DM patients. Primary outcomes included changes in bone mineral density (BMD), bone turnover markers, and fracture incidence. Results A total of 33 randomized controlled trials (33,107 participants) were included. GLP-1 RAs demonstrated improvements in BMD at the lumbar spine (0.052 g/cm2 [0.043–0.061]), total hip (0.047 g/cm2 [0.037–0.057]), and femoral neck (0.072 g/cm2 [0.060–0.084]), however BMD findings from studies less than 52 weeks require cautious interpretation per clinical densitometry standards. They reduced bone resorption (β-CTX SMD -0.36 [-0.53, -0.20]) while increasing formation markers, possibly normalizing the uncoupled remodeling characteristic of diabetic osteopathy. Long-term treatment was associated with reduced fracture risk by 20% (RR 0.80 [0.65–0.94]). Conclusions GLP-1 RAs may provide skeletal benefits in T2DM patients by addressing specific mechanisms underlying diabetic osteopathy. The skeletal effects appear to vary according to agent type, patient characteristics, and treatment duration, suggesting promising role for personalized approaches to therapy selection. When bone health is a concern, GLP-1 RAs may represent a beneficial therapeutic option that could simultaneously address both metabolic and skeletal outcomes in patients with T2DM, though further bone-specific studies is needed for newer agents.